Feeling Pressure to Be a Perfect Mother Relates to Parental Burnout and Career Ambitions - Meeussen, Loes; Van Laar, Colette (Frontiers in Psychology, 2018)
Background & aims. Intensive mothering norms prescribe women to be perfect mothers. Recent research has shown that women’s experiences of pressure towards perfect parenting are related to higher levels of guilt and stress. The current paper follows up on this research with two aims: First, we examine how mothers regulate pressure towards perfect mothering affectively, cognitively, and behaviorally, and how such regulation may relate to parental burnout. Second, we examine how feeling pressure towards perfect mothering may spill over into mothers’ work outcomes. Methods. Through Prolific Academic, an online survey was sent to fulltime working mothers in the UK and USA with at least one child living at home (N = 169). Data were analyzed using bootstrapping mediation models. Results. Feeling pressure to be a perfect mother was positively related to parental burnout, and this relation was mediated by parental stress, by a stronger cognitive prevention focus aimed at avoiding mistakes as a mother, and by higher maternal gatekeeping behaviors taking over family tasks from one’s partner. Moreover, pressure towards perfect mothering had a positive direct effect on career ambitions; and a negative indirect effect, such that mothers with higher felt pressure towards perfect mothering experienced lower work-family balance, which in turn related to lower career ambitions. Conclusion. The findings suggest that intensive mothering norms might have severe costs for women’s family and work outcomes, and provide insights into where to direct efforts to reduce motherhood hardships and protect women’s career ambitions.